Estudo da fotocatálise heterogênea sobre Ti/TiO2 na descoloração de corantes sintéticos A heterogeneous photocatalysis study of decolorization of synthetic dyes on Ti/TiO - Thiago N. M. Cervantes; Dimas A. M. Zaia; Henrique de Santana (Química Nova, 2009)
The main goal of this paper was to study the degradation of synthetic dyes using photoelectrocatalytic properties of particulate films of TiO2 supported on plates of titanium and stimulated by UV-Vis radiation. The dyes decolorizations were measured using spectrophotometric methods to verify which the conditions on Ti/TiO2 electrode was the best for the photoelectrodegradation of them. The results showed that decolorization rates were higher than 90% during a period of 270 min. FT-IR spectroscopy showed that intermediate substances were formed after the decolorization and N=N group/aromatic structures were preserved independently of the specific structure of the dyes.